Effectiveness of the mechanisms of fraud prevention and detection in Nigeria - Efiong, Eme J.; Inyang, Inyang O.; Joshua, Udeme (Advances in Social Sciences Research Journal, 2016)
Whereas the problem of fraud is a global one, the rate and extent to which it is perpetrated in Nigeria, particularly in the public sector, is quite high and alarming. Literature reveals that different fraud prevention and detection mechanisms are being adopted to combat the menace of fraud. Forensic accounting techniques appears to be the most effective and are currently used in most developed countries of the world. However, the extent to which forensic accounting techniques are being applied in fraud prevention and detection in Nigeria is not known.This study was therefore aimed at investigating the mechanisms of fraud prevention and detection, and their levels of effectiveness in Nigeria.The study involved the collection of quantitative data from accounting practitioners. The questionnaire served as the survey instrument.The study identified several fraud prevention and detection mechanisms that are currently used in Nigeria, such as systems of internal controls, operational audits and corporate code of conduct. Students’ t-test indicates a significant difference between the perceived effectiveness and actual usage of fraud prevention and detection mechanisms in Nigeria. It was further discovered that the most effective mechanisms, like the forensic accounting techniques, are the least used in fraud prevention and detection. This implies that the current mechanisms of fraud prevention and detection are not proactive in dealing with the fraud menace. The study recommended that proactive measures in terms of mechanisms be employed in tackling fraud manace in Nigeria.